Suppression of the GTPase-activating protein RGS10 increases Rheb-GTP and mTOR signaling in ovarian cancer cells. Issue 1 (1st December 2015) - Altman, Molly K.; Alshamrani, Ali A.; Jia, Wei; Nguyen, Ha T.; Fambrough, Jada M.; Tran, Sterling K.; Patel, Mihir B.; Hoseinzadeh, Pooya; Beedle, Aaron M.; Murph, Mandi M.
Highlights RGS10 suppression triggers phosphorylation of mTOR, 4E-BP1, p70S6K and rProtein-S6. Rheb-GTP is increased in ovarian cancer cells after RGS10 suppression. Suppression of RGS10 increases cell proliferation in the presence of chemotherapy. Effects of RGS10 suppression occur in serum-free conditions with low nutrients.